Estimation of the symptoms for GERD by GerdQ in the patients with rheumatic diseases. Issue 2 (3rd March 2016) - Nozaki, Yuji; Kinoshita, Koji; Ri, Jinhai; Sakai, Kenji; Shiga, Toshihiko; Hino, Shoichi; Hirooka, Yasuaki; Sugiyama, Masahumi; Funauchi, Masanori; Matsumura, Itaru
Abstract: Objective : Gastroesophageal reflux disease (GERD) is one of the most common comorbidity in many diseases, but the frequency in rheumatic disease has not been well understood. Methods : We investigated the prevalence of GERD by GerdQ in 530 rheumatic patients [systematic lupus erythematosus (SLE; n  = 120), rheumatoid arthritis (RA; n  = 117), polymyalgia rheumatica (PMR; n  = 40), dermatomyositis and polymyositis (PM/DM; n  = 38), systemic scleroderma (SSc; n  = 37), mixed connective tissue disease (MCTD; n  = 18), Behçet disease (BD; n  = 17), adult onset still disease (AOSD; n  = 14), and other rheumatic diseases ( n  = 129)]. Results : The mean GerdQ scores of patients was 6.2 ± 1.8, respectively, and no significant differences were observed between all patients. However, the GERD prevalence in SSc and BD was increased compared to that in SLE, RA, PMR, PM/DM, MCTD, and AOSD. In no medication of proton pump inhibitors (PPIs), a significant increase in the risk of GERD symptoms was 2.5 times compared with that in the medication of PPIs in all patients by multivariable regression analysis. On the other hand, there were no increased risks of GERD symptoms with corticosteroids. Conclusion : In rheumatic diseases, GerdQ would be the useful tool of diagnosis GERD, regardless whether the patients complain or not about gastrointestinal (GI) symptoms.